CARP VIII antibody-related autoimmune cerebellar ataxia in a child after Mycoplasma pneumoniae infection: a case report - Li, Minglei; Han, Zongming; Li, Jinlei; Wang, Qianyun; Lv, Zufang (Frontiers in Immunology, 2025)
Autoimmune cerebellar ataxia (ACA) is a cerebellar syndrome induced by autoimmune reactions and its onset is induced by malignant tumors, prodromic infection, and gluten allergy. Its clinical symptoms include gait disorder, limb ataxia, dysarthria, and dysphagia. According to the Chinese Expert Consensus on the Diagnosis and Management of Autoimmune Encephalitis 2024, the diagnosis of ACA is based on the following points: 1. subacute or acute onset of the disease, with cerebellar syndrome as the main manifestation; 2. The cranial magnetic resonance imaging (MRI) in the early stage of the disease (within three months) does not show significant atrophy of the cerebellum and brainstem; 3. presence of either of the following: 1) positive anti-cerebellar antibodies in serum and/or cerebrospinal fluid cell-based assay (CBA), 2) at least two of the following are present: ① the patient or first-degree relative has a history of autoimmune disease, ② cerebrospinal fluid leukocytes >5×106/L, or positive for cerebrospinal fluid specific oligoclonal bands, ③ tissue-based assay (TBA) revealing the characteristic fluorescent form of Purkinje cell antibody, and ④ the presence of systemic autoimmune disease-related antibodies; and 4. the absence of other diseases. Currently, fewer instances of ACA have been associated with positive results for carbonic anhydrase-related protein VIII (CARP VIII). Three case reports have been detected by this antibody in adults with ovarian cancer, breast cancer, or melanoma, and there is no report on this antibody in children. Moreover, neurological diseases associated with mycoplasma pneumoniae infection are increasingly being reported. Therefore, the correlation between this infection and autoimmune encephalitis antibodies needs to be further investigated.